Hubungan Intensitas Penggunaan Media Sosial Dengan Kecenderungan Nomophobia Pada Remaja Kelas 12 SMK An – Nahl Cibeber Kabupaten Cianjur Tahun 2022 - Hana Hamidah; Ahmad Rizal; Agus Purnama (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Background: With the development of technology, convenient access is easy to obtain with just a smartphone. This triggers teenagers to use smartphones in their daily lives to open social media or search for information. When use increases and is uncontrolled, it can cause anxiety if you are far away or cannot access a smartphone, which is called nomophobia. Objective: To determine the relationship between the intensity of social media use and the tendency to nomophobia. Method: This research uses a quantitative correlation research design with a cross approach method. sectional and Spearman rank using a simple random sampling model. Results: This study shows that there is a significant relationship between the intensity of social media use and the tendency to nomophobia with a significant value of 0.033 (p < 0.05) and a correlation value of 0.222 which is positive, meaning the higher the intensity of use social media, the higher the tendency to nomophobia. Conclusion: There is a relationship between the intensity of social media use and the tendency to nomophobia in grade 12 teenagers at An-Nahl Vocational School based on the results of data processing using the Spearman rank test method.